Non-compliance: the Achilles' heel of anti-fracture efficacy. - Seeman, E; Compston, J; Adachi, J; Brandi, M; Cooper, C; Dawson-Hughes, B; Jönsson, B; Pols, H; Cramer, J (2007)
About 50% of patients fail to comply or persist with anti-osteoporosis treatment regimens within 1 year. Poor compliance is associated with higher fracture rates. Causes of poor compliance are unknown. As it is not possible to predict poor compliance, close monitoring of compliance is needed. Despite evidence supporting the anti-fracture efficacy of several pharmacological agents, approximately 50% of patients do not follow their prescribed treatment regimen and/or discontinue treatment within 1 year. Poor compliance is associated with higher fracture rates and increased morbidity, mortality and cost. However, as poor compliance, even to placebo, is associated with adverse outcomes, the higher morbidity appears to be only partly the result of lack of treatment: as yet, undefined characteristics place poor compliers at higher risk of morbidity and mortality. Only a small proportion (e.g., 6%) of the variability in compliance is explained by putative causal factors such as older age, co-morbidity or greater number of medications. Regimens with longer dosing intervals, such as weekly dosing, improve compliance, persistence and outcomes, but only modestly. As it is not possible to predict poor compliance, close monitoring of compliance should be an obligatory duty in clinical care. How this is best achieved has yet to be established, but poor persistence occurs as early as 3 months of starting treatment, indicating the need for early monitoring.